DEVELOPMENT OF PROFESSIONAL COMPETENCE OF FUTURE PRIMARY TEACHERS BASED ON PEDAGOGICAL COACHING IN HIGHER EDUCATION (Universal International Scientific Journal, 2026)
This article discusses the conceptual foundations, practical mechanisms, and assessment tools for developing professional competence of future primary school teachers based on the pedagogical coaching approach in higher education. The study was developed based on the competency approach, reflective learning, collaborative learning, and structured models of coaching. An integrated model of “coaching session, microteaching, rubric/checklist, peer-feedback, reflective diary” is proposed as a methodological solution.
Keywords: pedagogical coaching; professional competence; reflection